DESAIN PEMBELAJARAN AKHLAK DI SEKOLAH (Studi pada SDIT Alam Nurul Islam Dua Ngawi) - Darmanto (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to determine the design of student moral learning at SDIT Alam Nurul Islam Dua Ngawi. This research is qualitative research with a case study type of research. This research used a purposive technique with the research subjects being the homeroom teacher and the supervisor, and the informants were the school principal, curriculum teacher, student affairs teacher, SIP supervisor, and student guardians. Data collection through observation, documentation and interviews. The results of the research show that the student moral learning design at SDIT Alam Nurul Islam Dua Ngawi is implemented in several ways, namely: integrating into all subjects which can be seen in the weekly learning plan, developing school culture through familiarizing Islamic activities in the school environment, extracurricular activities namely by always instilling commendable morals into every extracurricular activity, and community-based design by establishing class councils and school committee boards as concepts and correctors for school development activities and instilling student morals.